IMPROVING STUDENT’S ACHIEVEMENT IN WRITING REPORT BY USING CONTEXTUAL TEACHING AND LEARNING (CTL) STRATEGY - Jelita Panggabean and Johan Sinulingga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study deals with the improvement of the students’ achievement in report writing by using Contextual Teaching and Learning (CTL) strategy. This study tries to find out to what extent using CTL could improve students’ report writing. Subject of the study this research was the 2012/2013 second year – students of SMA Santo Thomas 4 Binjai, Medan. There were two kinds of data collected during the study, qualitative and quantitative data. The instrument for collecting the quantitative data was writing test while the qualitative data were diary notes, observation sheet, and questionnaire sheet. The qualitative data showed that the students were interested in the Contextual Teaching and learning (CTL) strategy. Based on the data analysis, the mean of the students score for the orientation test was 53.28, for the first cycle was 71.42 and second cycle was 84.28. The conclusion is that the Contextual Teaching and Learning (CTL) strategy can improve the student’s report writing Achievement.